2016
DOI: 10.1049/iet-cvi.2016.0244
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic mass classification according to Bi‐RADS lexicon

Abstract: The goal of this study is to propose a computer-aided diagnosis system to differentiate between four breast imaging reporting and data system (Bi-RADS) classes in digitised mammograms. This system is inspired by the approach of the doctor during the radiologic examination as it was agreed in BI-RADS, where masses are described by their form, their boundary and their density. The segmentation of masses in the authors' approach is manual because it is supposed that the detection is already made. When the segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…In addition to the mass size, the BI-RADS mammography [7] reported that the patient's age is necessary for the categorization of mammograms as it has the ability to change the assessment category of the lesion (downgrade or upgrade the BI-RADS category). This issue was also formerly discussed in the works of Lo et al [43], Gupta et al [5], and Chokri and Farida [18], in which the age has been found as an important discriminatory feature for the BI-RADS-based CAD systems. Table 1 provides a summary of the aforementioned quantified BI-RADS features.…”
Section: Additional Featuresmentioning
confidence: 81%
See 4 more Smart Citations
“…In addition to the mass size, the BI-RADS mammography [7] reported that the patient's age is necessary for the categorization of mammograms as it has the ability to change the assessment category of the lesion (downgrade or upgrade the BI-RADS category). This issue was also formerly discussed in the works of Lo et al [43], Gupta et al [5], and Chokri and Farida [18], in which the age has been found as an important discriminatory feature for the BI-RADS-based CAD systems. Table 1 provides a summary of the aforementioned quantified BI-RADS features.…”
Section: Additional Featuresmentioning
confidence: 81%
“…However, the above-mentioned works focused on discriminating mammogram benign lesions from malignant or normal from abnormal, while few studies have reported the BI-RADS classification of breast masses using mammograms. The authors in [18] introduced an automatic CAD system to classify mammographic masses either as benign or as malignant or in four BI-RADS categories (B-2, B-3, B-4, and B-5). A set of 23 handcrafted features was extracted and fed into a multilayer perceptron for classification.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
See 3 more Smart Citations